Design and implementation of bio inspired hexapod for exploration applications. (2021) - Deepa, T.; Angalaeswari, S.; Subbulekshmi, D.; Krithiga, S.; Sujeeth, S.; Kathiravan, Raja
Abstract: With advances in Robotics, robots of different kinds are increasingly being used for scientific discoveries and unmanned missions ranging from Under ocean research to Extra-terrestrial exploration. Prominent missions that heavily used Robots include Exploration and Excavation, Unmanned Mining and Bomb defusal, Complex Terrain mapping and Geo-Surveying, Remote Surveillance and other Military activities. There are a various type of robots mainly classified on the basis of Control type – Autonomous, Semi-Autonomous and Manual; Locomotion Mechanism – Legged, Rover and Hybrid. While each type has its own advantages and drawbacks, the suitability of each type depends on its target application. This paper aims to design, develop and test an Autonomous robot, inspired from Biological evolution of Insects, suitable for unmanned exploration missions.